Evaluation of biomass production of CO-3 fodder grass under coconut and its effect on nut yield of intermediate zone coconut plantations in Sri Lanka - Senarathne, S.H.S.; Raveendra, S. A. S. T.; Udumann, S. S.; Kumara, M. A. N. A. (International Coconut Community Journal, 2023)
Six CO-3 fodder grass planting systems under coconut palms were evaluated for six years concerning biomass production and coconut yield. This study was carried out at Potthukulama (PRS) Research Station of the Coconut Research Institute, in the Low Country Dry Zone of the Northwestern province of Sri Lanka, where the soil series is Ambakele. According to the experiment results, the highest CO-3 biomass was produced when five CO-3 rows were planted between coconut rows and harvested in 30 days lopping interval. There was no significant effect of CO-3 planting densities and lopping intervals on the yield of coconut.